Determinants of electric motorbike purchasing intention among consumers in Hanoi City, Vietnam - Tran Thi Lan Phuong; Tran Thi Lan Huong; Tran Tho Dat; Dinh Duc Truong (Environmental Research Communications, 2024)
Climate change is one of the biggest challenges facing human development in the coming decades. To cope with climate change, greening transportation becomes one of the most important solutions, including the key role of consumers. This study aimed to determine the factors affecting customer’s intention to buy electric motobikes in Hanoi, Vietnam. We used the theory of planned behavior to develop research models. Study data was collected by convenient sampling method through a survey with 600 participants in Hanoi. The study used SPSS 22.0 software to perform descriptive statistics, Cronbach’s Alpha test, Exploring Factor Analysis and multiple linear regression for data processing. The results showed six factors including Environmental awareness, Attitude, Perceived behavioral control, Attractiveness of other means, Subjective norms and Promotion policies had significant impact on the customers’ intention to buy electric motorbikes, of which factor Attractiveness of other means had the most decisive influence. From results, the paper discussed and gave some managerial implications to enhance the intention to buy electric motorbikes of people in Hanoi and expand proposals to other cities in Vietnam.